PENGARUH TEAMWORK DAN LOYALITAS TERHADAP KINERJA KARYAWAN DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERASI - Endah Widiyanti, Suprayitno & Sutarno (Universitas Slamet Riyadi, 2017)
The purpose of this reserch was to analyze the significcant effect of teamwork,loyalty and leadership on empoyees performance and to analyze the effect of teamworkand loyalty to employees performance with leadership are moderated variable. Thisresearch is a survey. The population are employees of warehouse at PT Rosalia ExpressPalur totaling 30 people so the whole is used as a sample with total sampling technique.Data collection techniques used questionnaire and observation. Data analysistechniques used multiple linear regression and absolute difference test. The resultsshowed that teamwork has a significant effect on employees performance. Loyalty has asignificant effect on employees performance. Leadership has a significant effect onemployees performance. Leadership does not moderate the effect of teamwork andloyalty to employees performanceKeywords: teamwork, loyalty, leadership, performance